Variability of clinical target volume delineation for rectal cancer patients planned for neoadjuvant radiotherapy with the aid of the platform Anatom-e. (June 2018) - Franco, Pierfrancesco; Arcadipane, Francesca; Trino, Elisabetta; Gallio, Elena; Martini, Stefania; Iorio, Giuseppe Carlo; Piva, Cristina; Moretto, Francesco; Ruo Redda, Maria Grazia; Verna, Roberta; Tseroni, Vassiliki; Bona, Cristina; et al.
Highlights: Delineation of treatment volumes is a major source of uncertainties in rectal cancer radiotherapy. Anatom-e is an electronic platform working as an image-based delineation system. The use of Anatom-e was able to decrease the inter-observer variability in the delineation process of clinical target volumes for locally advanced rectal cancer. Anatom-e may be potentially helpful in increasing the compliance to common guidelines and protocols. Abstract: Objective: Delineation of treatment volumes is a major source of uncertainties in radiotherapy (RT). This is also true for rectal cancer patients undergoing neoadjuvant RT, with a potential impact on treatment quality. We investigated the role of the digital platform Anatom-e (Anatom-e Information Sytems Ltd., Houston, Texas) in increasing the compliance to follow a specific treatment protocol in a multicentric setting. Materials and methods: Two clinical cases of locally advanced rectal cancer were chosen. Participants were instructed to follow the 2009 Radiation Therapy Oncology Group consensus atlas and asked to manually segment clinical target volumes (CTVs), for both patient 1 and 2, on day 1 with and without the use of Anatom-e. After one week (day 2), the same radiation oncologist contoured again, with and without Anatom-e, the same CT series. Intraobserver (Intra-OV) and interobserver (Inter-OV) variability were evaluated with the Dice similarity coefficient (DSC), the Hausdorff distance (HD) and mean distance to agreement (MDA). Results: For clinical case 1, no significant difference was found for Intra-OV and Inter-OV. For clinical case 2, no significant difference was found for Intra-OV but a statistically significant difference was found for Inter-OV in DSC when using or not the platform. Mean DCS was 0.65 (SD: ±0.64; range: 0.58–0.79) for day 1 vs reference volume without Anatom-e and 0.72 (SD: ±0.39; range: 0.67–0.77) (p = 0.03) with it. Mean MDA was lower with Anatom-e (3.61; SD: ±1.33; range: 2.85–4.78) than without (4.14; SD: ±2.97; range: 2.18–5.21), with no statistical significance (p = 0.21) The use of Anatom-e decreased the SD from 2.97 to 1.33. Mean HD was lower with Anatom-e (26.06; SD: ±2.05; range: 24.08–32.62), with no statistical significance (p = 0.14) compared to that without (31.39; SD: ±1.31; range: 26.14–48.72). Conclusions: The use of Anatom-e decreased the Inter-OV in the CTV delineation process for locally advanced rectal cancer with complex disease presentation planned for neoadjuvant RT. This system may be potentially helpful in increasing the compliance to follow shared guidelines and protocols.